ON AMBIGUITY AND INCONGRUITY OF TERMS IN TRANSLATIONS OF INTERNATIONAL TREATIES - Parent, Arnaud (Vertimo studijos, 2017)
The aim of this article is to study the ambiguity and incongruity of terms in translation of international treaties, how they may present themselves and their impact on international relations.